Nab-paclitaxel and gemcitabine or FOLFIRINOX as first-line treatment in patients with unresectable adenocarcinoma of the pancreas: does sequence matter? - Ursula M. Vogl (BMC Cancer, 2019)
Abstract Background Locally advanced or metastatic adenocarcinoma of the pancreas remains - despite the implementation of new chemotherapy protocols - a disease with short overall survival (OS). Methods Eighty-three patients were treated with locally advanced or metastatic adenocarcinoma of the pancreas with either FOLFIRINOX or nab-Paclitxel and Gemcitabine (nabPGem) as first- or second line therapy. We analysed the outcome for OS and progression-free survival (PFS) in terms of treatment regimen and sequence. Results The majority of patients presented in good performance status (PS) with a median age of 68 years. Fourty-two patients received FOLFIRINOX as first-line therapy, 41 patients were treated with nabPGem as first line therapy. Forty-eight patients received both treatments. The OS of all 83 patients was 12.6 months (95% CI: 10.7–14.6), resulting in a 1-year OS of 54%. Forty-eight patients received FOLFIRINOX followed by nabPGem or vice versa. There was no significant difference in OS or PFS for either of the two sequences (p = 0.9). The OS for FOLFIRINOX followed by nabPGem or nabPGem followed by FOLFIRINOX was 13.7 months (95% CI: 12.6–14.7) and 13.8 months (95% CI: 8.6–19), respectively. Conclusions The sequence FOLFIRINOX followed by nab-Paclitaxel and Gemcitabine or vice versa lead to an equal OS outcome.